Synchronization between fractional-order ravinovich-fabrikant and lotka-volterra systems - Agrawal S.K.; Srivastava M.; Das S. (My University, 2025)
This article examines the synchronization performance between two fractional-order systems, viz., the Ravinovich-Fabrikant chaotic system as drive system and the Lotka-Volterra system as response system. The chaotic attractors of the systems are found for fractional-order time derivatives described in Caputo sense. Numerical simulation results which are carried out using Adams-Boshforth-Moulton method show that the method is reliable and effective for synchronization of nonlinear dynamical evolutionary systems. Effects on synchronization time due to the presence of fractional-order derivative are the key features of the present article. © Springer Science+Business Media B.V. 2012.